O papel de recursos tecnológicos no processo de aprendizagem de bateria. - Potiguara, Lucas Benjamin (2021)
This text has as its theme technology as a resource in learning the battery. This is a course conclusion work (monograph) and has the general objective: to understand the role of technological resources in the instrument learning process for drum students in the music degree course at UFPB. The specific objectives are: to analyze which technologies are present in the battery study process and how they are used by students; discuss challenges and possibilities of using electronic resources for battery learning; verify the articulation of technological resources in the UFPB battery classes. The methodology consisted of a qualitative study having as data source: bibliographical research and collective interview with UFPB drum students. The literature review points out that there is a unity in relation to the potential of technological transformations in the ways of learning, teaching and consuming music, mainly focusing on the use of technology in the instrument's teaching-learning process. But it is also possible to notice a gap when we try to deal with the teaching-learning of battery combined with technology, using this as a resource for learning. The main results show that the use of technological resources can provide the development of different battery learning experiences, such as the development of autonomy and self-learning.